Intelligent Sensors for Human Motion Analysis - Krzeszowski, Tomasz; Świtoński, Adam; Kepski, Michal; Calafate, Carlos Tavares (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book, "Intelligent Sensors for Human Motion Analysis," contains 17 articles published in the Special Issue of the Sensors journal. These articles deal with many aspects related to the analysis of human movement. New techniques and methods for pose estimation, gait recognition, and fall detection have been proposed and verified. Some of them will trigger further research, and some may become the backbone of commercial systems.